A subpopulation of agouti-related peptide neurons exciting corticotropin-releasing hormone axon terminals in median eminence led to hypothalamic-pituitary-adrenal axis activation in response to food restriction - Yesmin, Ruksana; Watanabe, Miho; Sinha, Adya Saran; Ishibashi, Masaru; Wang, Tianying; Fukuda, Atsuo (Frontiers in Molecular Neuroscience, 2022)
The excitatory action of gamma-aminobutyric-acid (GABA) in the median-eminence (ME) led to the steady-state release of corticotropin-releasing hormone (CRH) from CRH axon terminals, which modulates the hypothalamic-pituitary-adrenal (HPA) axis. However, in ME, the source of excitatory GABAergic input is unknown. We examined agouti-related peptide (AgRP) expressing neurons in the arcuate nucleus as a possible source for excitatory GABAergic input. Here, we show that a subpopulation of activated AgRP neurons directly project to the CRH axon terminals in ME elevates serum corticosterone levels in 60% food-restricted mice. This increase in serum corticosterone is not dependent on activation of CRH neuronal soma in the paraventricular nucleus. Furthermore, conditional deletion of Na+-K+-2Cl− cotransporter-1 (NKCC1), which promotes depolarizing GABA action, from the CRH axon terminals results in significantly lower corticosterone levels in response to food restriction. These findings highlight the important role of a subset of AgRP neurons in HPA axis modulation via NKCC1-dependent GABAergic excitation in ME.